Comprehensive analysis of advanced glycation end-products in commonly consumed foods: presenting a database for dietary AGEs and associated exposure assessment - Qiaozhi Zhang; Huatao Li; Ruixing Zheng; Lili Cao; Shufen Zhang; Shuifeng Zhang; Huadong Sheng; Yuhao Jiang; Yanbo Wang; Linglin Fu (Food Science and Human Wellness)
Advanced glycation end-products (AGEs) are a group of heterogeneous compounds formed in heat-processed foods and are proven to be detrimental to human health. Currently, there is no comprehensive database for AGEs in foods that covers the entire range of food categories, which limits the accurate risk assessment of dietary AGEs in human diseases. In this study, we first established an isotope dilution UHPLC-QqQ-MS/MS-based method for simultaneous quantification of 10 major AGEs in foods. The contents of these AGEs were detected in 334 foods covering all main groups consumed in Western and Chinese populations. Nε-Carboxymethyllysine, methylglyoxal-derived hydroimidazolone isomers, and glyoxal-derived hydroimidazolone-1 are predominant AGEs found in most foodstuffs. Total amounts of AGEs were high in processed nuts, bakery products, and certain types of cereals and meats (> 150 mg/kg), while low in dairy products, vegetables, fruits, and beverages (< 40 mg/kg). Assessment of estimated daily intake implied that the contribution of food groups to daily AGE intake varied a lot under different eating patterns, and selection of high-AGE foods leads to up to a 2.7-fold higher intake of AGEs through daily meals. The presented AGE database allows accurate assessment of dietary exposure to these glycotoxins to explore their physiological impacts on human health.